Ultralow-voltage-drop GaN/InGaN/GaN tunnel junctions with 12% indium content. (7th November 2017) - Akyol, Fatih; Zhang, Yuewei; Krishnamoorthy, Sriram; Rajan, Siddharth
Abstract: We report a combination of highly doped layers and polarization engineering that achieves highly efficient blue-transparent GaN/InGaN/GaN tunnel junctions (In content = 12%). NPN diode structures with a low voltage drop of 4.04 V at 5 kA/cm 2 and a differential resistance of 6.51 × 10 −5 Ω·cm 2 at 3 kA/cm 2 were obtained. The tunnel junction design with n ++ -GaN (Si: 5 × 10 20 cm −3 )/3 nm p ++ -In0.12 Ga0.88 N (Mg: 1.5 × 10 20 cm −3 )/p ++ -GaN (Mg: 5 × 10 20 cm −3 ) showed the best device performance. Device simulations agree well with the experimentally determined optimal design. The combination of low In composition and high doping can facilitate lower tunneling resistance for blue-transparent light-emitting diodes.